Protocolo para determinar in vivo la resistencia a la extracción axial de tornillos poliaxiales de implantes de columna cervical. Prevalidación in vitro - Noriega, Zeferino Damián; Puerta-Huerta, J. Pedro A.; Cuéllar-Puente, J. Antonio (Revista Mexicana de Ingenieria Biomedica, 2004)
To assure the biomechanical stability of cranio-vertebral fixation systems of polyaxial screws (PAS) and longitudinal plates, up to date the axial pullout strength (APS) of the PAS is in vitro experimentally determined, demanding the use of expensive hardware and human cadaveric tissue. Therefore, a novel in vivo tests protocol for determining the APS of the PAS is presented in this work. For this purpose, a stainless steel mechanical device was designed for applying a “tightening torque” (TT) and to pull out in vivo the PAS. The protocol was pre-validated in vitro, using porcine and bovine bone. The APS was calculated by using the respective equation, taking into account the ultimate TT. The mean APS for the PAS inserted in porcine bone was 790 ± N (n = 5). One of the PAS inserted in the bovine bone was fractured and its APS calculated was 5.028 kN. The mean APS obtained for other five tests was 2.05 ± 0.267 kN. In vitro tests will be performed applying axial pullout force for determining the torsion coefficient for the steel-bronze contact, before the in vivo tests. The final execution of this protocol will demand a low-cost hardware.